The be book : a journey into miracles and self-liberation - Maryel, Mynoo (Ahmedabad : Jaico Publishing House, 2017)
Mynoo Maryel stepped away from her hamster-on-a-wheel life and leapt out into the great unknown. She learned to become still. We can all do this. Absolute miracles are there for each of us to claim. All that's required are some timely reminders, and something wonderful to light our way. The BE Book offers us those reminders, and that light.
Include glossary.
Keywords: Autobiography